Impacts of COVID-19 on nursing care in the head and neck oncology outpatient clinic - Santos, Lucimere Maria dos; Santos, Marcia; Palermo, Teresa Cristina Silva; Santos, Luciana Nogueira dos; Silva, Cristiane dos Santos Mendonça da; Marinho, Aureonice; Peragene, Aline; Titulação, Julia Meireles da Costa (Seven Editora, 2023)
This study aims to analyze the impacts of COVID-19 on the care of cancer patients in the head and neck surgery outpatient clinic, through the procedures performed in the years 2019, 2020, and 2021. Method: Qualitative, descriptive study about the procedures performed by the nursing team in a head and neck surgery outpatient clinic. Data were collected from January 2019 to December 2021 and computed in an Excel spreadsheet. Results: They showed a negative disparity in the quantity of patient care in the head and neck surgery outpatient clinic in 2019 compared to 2020, in which there was a decrease of 33%. Comparing the results of the year 2019 with 2021 we noticed a drop of 25%. However, when compared to the year 2020 to 2021, there was an increase of 12%. In the number of procedures performed in 2020, there was a decrease of 31% compared to 2019, and, compared to 2021, there was a decrease of 26%, but in the year 2020 to 2021, there was an increase of 13%. Conclusion: The COVID-19 pandemic generated a strong impact on the care provided to patients of the head and neck surgery outpatient clinic, leading to a reduction in the care and provision of nursing care to this clientele, but at the beginning of the pandemic scenario the institutions had to redesign the care protocols to cope with the current situation of the country and the world, thus promoting safer and more efficient assistance. DOI:https://doi.org/10.56238/emerrelcovid19-007